Characteristics and outcome differences in male and female oral cavity cancer patients in Taiwan. Issue 44 (5th November 2021) - Lee, Yi-Chieh; Young, Chi-Kuang; Chien, Huei-Tzu; Chin, Shy-Chyi; Landelli, Andrea; Liao, Chun-Ta; Tsao, Chung-Kang; Kang, Chung-Jan; Huang, Shiang-Fu
Abstract : Abstract: Oral cavity squamous cell carcinoma (OSCC) is a leading cause of death in Taiwan. Most of the patients in the literature are male. The risk factors, cancer characteristics, and treatment outcomes were investigated in female patients and compared with male patients in this study. This retrospective study recruited 2046 OSCC patients between 1995 and 2019. The age, tumor subsites, and survival were reviewed and recorded. Overall survival and disease-free survival were the main outcomes. Female patients represented 6.7% of the entire study cohort. Females were diagnosed at an older age and an earlier local stage than male patients ( P < .001). Female patients were less exposed to cigarettes, alcohol, and betel-quid (all P < .001). The tongue (55.1%) was the most frequent subsite in females, while the buccal cavity (38.4%) and the tongue (35.3%) were more likely ( P < .001) to be associated with the male gender. Female patients in the tongue cancer subgroup presented less frequently with extra-nodal extension compared with male patients ( P = .040). No significant differences in recurrence or overall deaths were observed between the genders during the follow-up period. The OSCC male to female ratio in Taiwan was 14:1. Female OSCC occurred more frequently on the tongue, and was diagnosed at an older age and at an earlier tumor stage than in male patients. No survival difference was found between female and male OSCC patients.